Comparing small mammal assemblages between communal and commercial rangelands within a region of the Succulent Karoo, South Africa - Haveron, Sara Elizabeth (Stellenbosch : Stellenbosch University, 2008)
Thesis (MScConsEcol (Conservation Ecology and Entomology))--Stellenbosch University, 2008.